Preparation and characterisation of tungstate scheelite structured nanoparticles - Zawawi, S.M.M.; Yahya, R.; Hassan, A.; Daud, M.N. (2011)
A series of tungstate scheelite structured MWO 4 (M=Ca, Sr, Pb and Ba) were synthesised using the sucrose solution evaporation method. Characterisation of these materials revealed that nanoparticles were formed, with the calcination temperature >400Â°C. The nanoparticle powders formed are crystalline and exist in its pure phase. It is found that the degree of crystalline products is low with the decrease in ionic radius (Ca<Sr<Pb<Ba), and also, diffraction peaks at the plane (112), (004) and (204) are shifted to lower angles (2Î¸) in accordance to the reduction in dhkl spacing. The S BET value of CaWO 4 gave the highest surface area (277Â·53 m 2 g -1) in the observed nanosize grain obtained from the field emission scanning electron microscopy image.